Kinematic Analysis of 3-SPS/UPR Parallel Worktable - Bai Xueqing; Wang Yuan; Li You (Jixie chuandong)
A worktable of 3-SPS/UPR parallel mechanism is proposed, which is used to assist the less degree of freedom machine tool to process the surface of the workpiece. The kinematic screw matrix of the 3-SPS/UPR parallel mechanism is established; its degree of freedom is analyzed by the screw theory and verified by the modified Kutzbach-Grübler formula; through the geometric relationship in the mechanism, the closed vector method is used to solve the inverse position solution of the mechanism, and the velocity Jacobian matrix of the mechanism is derived; the workspace of the mechanism is solved by three-dimensional dynamic search method; the kinematics of the parallel worktable is simulated by the Adams software. The 3-SPS/UPR parallel mechanism can carry out the movement of two translation and two rotation, improve the machining efficiency and quality of the machine tool, increase the machining range of the machine tool and improve the surface machining ability of the machine tool.